Cutting the forest down to save your face: Narcissistic national identification predicts support for anti-conservation policies. (October 2018) - Cislak, Aleksandra; Wojcik, Adrian Dominik; Cichocka, Aleksandra
Abstract: Past work showed that strong national identification is negatively related to environmental protection. In this paper we aim to demonstrate that only some forms of national identity oppose environmental concerns. In three studies, we examined the association between support for anti-conservation policies and narcissistic versus conventional national in-group identification. Collective narcissism is a belief in in-group greatness associated with the need for external validation. We found that national collective narcissism (but not national identification without the narcissistic component) was positively associated with support for government subsidy for the coal industry (Study 1, n  = 102), and logging the Bialowieza Forest (Study 2, n  = 189 and Study 3, n  = 635, nationally representative sample). In Studies 2 and 3 these effects were mediated by an increased need to make decisions independently of external influences. The role of defensive forms of in-group identification in support for environmental harm is discussed. Highlights: Anti-environmentalism is differentially related to various types of national identity. National narcissism predicted support for the coal industry and logging the Bialowieza Forest. This was due to the need to assert the image of the in-group as independent and strong. National identification was unrelated to support for anti-conservation government policies.